Entamoeba histolytica-secreted cysteine proteases induce IL-8 production in human mast cells via a PAR2-independent mechanism - Lee Young Ah; Nam Young Hee; Min Arim; Kim Kyeong Ah; Nozaki Tomoyoshi; Saito-Nakano Yumiko; Mirelman David; Shin Myeong Heon (Parasite, 2014)
Entamoeba histolytica is an extracellular tissue parasite causing colitis and occasional liver abscess in humans. E. histolytica-derived secretory products (SPs) contain large amounts of cysteine proteases (CPs), one of the important amoebic virulence factors. Although tissue-residing mast cells play an important role in the mucosal inflammatory response to this pathogen, it is not known whether the SPs induce mast cell activation. In this study, when human mast cells (HMC-1 cells) were stimulated with SPs collected from pathogenic wild-type amoebae, interleukin IL-8 mRNA expression and production were significantly increased compared with cells incubated with medium alone. Inhibition of CP activity in the SPs with heat or the CP inhibitor E64 resulted in significant reduction of IL-8 production. Moreover, SPs obtained from inhibitors of cysteine protease (ICP)-overexpressing amoebae with low CP activity showed weaker stimulatory effects on IL-8 production than the wild-type control. Preincubation of HMC-1 cells with antibodies to human protease-activated receptor 2 (PAR2) did not affect the SP-induced IL-8 production. These results suggest that cysteine proteases in E. histolytica-derived secretory products stimulate mast cells to produce IL-8 via a PAR2-independent mechanism, which contributes to IL-8-mediated tissue inflammatory responses during the early phase of human amoebiasis.